A recurrent germline mutation in the PIGA gene causes Simpson‐Golabi‐Behmel syndrome type 2. Issue 2 (6th November 2015) - Fauth, Christine; Steindl, Katharina; Toutain, Annick; Farrell, Sandra; Witsch‐Baumgartner, Martina; Karall, Daniela; Joset, Pascal; Böhm, Sebastian; Baumer, Alessandra; Maier, Oliver; Zschocke, Johannes; Weksberg, Rosanna; et al.
Abstract : Hypomorphic germline mutations in the PIGA (phosphatidylinositol glycan class A) gene recently were recognized as the cause of a clinically heterogeneous spectrum of X‐linked disorders including (i) early onset epileptic encephalopathy with severe muscular hypotonia, dysmorphism, multiple congenital anomalies, and early death ("MCAHS2"), (ii) neurodegenerative encephalopathy with systemic iron overload (ferro‐cerebro‐cutaneous syndrome, "FCCS"), and (iii) intellectual disability and seizures without dysmorphism. Previous studies showed that the recurrent PIGA germline mutation c.1234C>T (p.Arg412*) leads to a clinical phenotype at the most severe end of the spectrum associated with early infantile lethality. We identified three additional individuals from two unrelated families with the same PIGA mutation. Major clinical findings include early onset intractable epileptic encephalopathy with a burst‐suppression pattern on EEG, generalized muscular hypotonia, structural brain abnormalities, macrocephaly and increased birth weight, joint contractures, coarse facial features, widely spaced eyes, a short nose with anteverted nares, gingival overgrowth, a wide mouth, short limbs with short distal phalanges, and a small penis. Based on the phenotypic overlap with Simpson‐Golabi‐Behmel syndrome type 2 (SGBS2), we hypothesized that both disorders might have the same underlying cause. We were able to confirm the same c.1234C>T (p.Arg412*) mutation in the DNA sample from an affected fetus of the original family affected with SGBS2. We conclude that the recurrent PIGA germline mutation c.1234C>T leads to a recognizable clinical phenotype with a poor prognosis and is the cause of SGBS2. © 2015 Wiley Periodicals, Inc.